Temporal evolution of DMS and DMSP in Antarctic coastal seawater - GAMBARO A.; MORET I.; PIAZZA R.; DA RIN E.; CAPODAGLIO G.; BARBANTE C.; CESCON P.; ANDREOLI, CARLO (International Journal of Environmental Analytical Chemistry, 2004)
The temporal evolution of concentrations of dimethylsulphide (DMS), its precursor dimethylsulphoniopropionate (DMSP) and chlorophyll a is surveyed weekly in the water column and in a landfast ice core at a coastal station of Gerlache Inlet (Terra Nova Bay, Antarctica) from 27 November 2000 to 14 February 2001. The DMS and DMSP profile concentrations in the water column are similar and show a clear temporal trend, with minimum values (< 0.7 nM) at all depths occurring on 27 November 2000 and maximum values (4.8 x 10(2) nM for DMS and 1.8 x 10(2) nM for DMSP) in surface water on 27 December 2000 for DMS and on 19 December 2000 for DMSP. When the sea-ice cover is present, the temporal evolution of DMSP closely follows that of chlorophyll a in the water column, supporting the idea that DMSP, and therefore DMS, has a phytoplanktonic origin. However, when the ice cover breaks up during the late austral summer, a second phytoplankton bloom occurs, while the DMSP concentration in the sea-water column remains very low. In the ice core, the results show higher concentrations of DMSP than those of the underlying sea water, highlighting the important role of sea ice in the sulphur cycle of the Antarctic ecosystem.